EXPERIMENTAL ASSESSMENT OF ENERGY OF GEARING FLUCTUATION OF THE DYNAMIC COMPONENT OF THE TORQUE ON THE BIT - Moisyshyn V. М.; Ivasiutyn, A. P. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2024)
The purpose of the proposed article is to establish, based on the results of bench-scale experimental studies, the influence of rock hardness and external independent factors, which include the axial static load FCT, bit rotation frequency n, stiffness С and damping coefficient β of the drilling tool, on the energy of toothed oscillations of the dynamic component of the torque on chisels. Bench research was conducted according to the method of rational planning of experiments, according to which the combination of the listed independent factors occurs only once. The planned factorial experiment was carried out in sandstone blocks of the Vorotyshchensk world, composed of two interlayers with a hardness of 1440 and 2050 MPa. Constant factors during drilling in bench conditions were the type and diameter of the three-layer bit and the consumption of flushing fluid (water). According to the results of the research carried out in the layer with a hardness of 2050 MPa, the equation of the multifactorial empirical model of the energy of tooth oscillations of the dynamic component of the torque on the bit was constructed, the influence of external independent factors on this energy were analyzed, and the main patterns of changes in partial dependencies і on the rock hardness were established. We note that the results of bench research in a layer with a hardness of 1440 MPa were previously published by us in the article "Multifactorial empirical models of low-frequency and toothed oscillations of the dynamic component of the torque on the bit".